Fungsi Kehumasan Pada Pendamping PKH Di Kelurahan Ulujami Jakarta Selatan - Muhamad Syamsi; Winda Dwi Astuti Zebua (Institut Nalanda, 2024)
One party that plays an important role in public information disclosure is government public relations, which is obliged to provide information and outreach to the public. Public Relations of the Republic of Indonesia Ministry of Social Affairs, carries out government public relations functions for the Family Hope Program and also goes to the field to socialize a program run by the Republic of Indonesia Ministry of Social Affairs, so that the public gets information related to the Republic of Indonesia Ministry of Social Affairs program. This research aims to describe the function of government public relations in internal and external communication as well as the socialization of a PKH program owned by the Ministry of Social Affairs, as well as how it is completed. The theory used is the government's public relations function. The method used is descriptive with a qualitative approach. The information sources consisted of key informants and two informants, located at the Indonesian Ministry of Social Affairs and 1 informant from the PKH assistant and one community who received the PKH program and one community who did not receive the PKH program. The results of this research outline show that the public relations function of the Ministry of Social Affairs collaborates with several national and regional media to facilitate their outreach with the aim of conveying information to the public regarding the Ministry of Social's government programs.